Contributing factors for electricity storage in a carbon‐free power system. (8th September 2021) - Koivunen, Tero; Syri, Sanna; Veijalainen, Noora
Summary: The Government of Finland is targeting carbon neutrality by 2035. Increasing electrification emphasizes the need for significant emission reductions in power generation. As reduction in power generation emissions is partly realized by increase in intermittent energy sources, electricity storage may become an important part of a carbon neutral power system. This study investigates the behavior of electrical storages as a part of a large‐scale national carbon‐free power system model. As a case study, a three‐year model of a carbon‐free Finnish power system set in 2050 with the aim to identify various factors affecting electricity storage, and the results are compared with literature. The proposed case study features various scenarios with a national power system with very high amounts of renewables and a significant hydro capacity, while amount of combustion‐based energy production is minimal. In addition, hydrological stress scenarios representing historically severe drought years were introduced. The amount of electricity storage needed was found to be most affected by nuclear and electricity trading capacities, which is consistent with literature findings. The data period used as basis for modeling also affected the need for electricity storage, as interannual variations in renewable production were found to have a large effect on modeled results. The needed electricity storage capacities increased significantly in the stress scenarios. The electricity storage need was found to be seasonal in nature, but this may be partly due to missing demand flexibility within the modeled power system, which caused very large individual storage discharge peaks. The results emphasize the need to take several years of historical data into account to ensure system availability in different conditions. Highlights: Nuclear energy was found to decrease system costs in a 100% carbon‐free power system. Multi‐year modeling is essential to secure system availability due to the important role of hydropower and seasonal wind variability. Electricity storages were found to be seasonal in nature. The main reason was exceptionally low windiness during individual periods, which resulted in large but temporarily short power deficits due to insufficient flexibility obtained from hydropower and power imports. This was especially evident in stress scenarios and mainly contributed to the higher costs in low‐nuclear scenarios. Detailed hydropower modelling of historically exceptional dry seasons in Finland was utilized as one stress scenario. Exceptionally, dry long‐term period increased the need for electricity storages significantly due to the lost flexibility offered by hydro and reduced electricity import capacities. Abstract : Contributing factors for electrical storage in a carbon‐free power system by Tero Koivunen*, Sanna Syri, and Noora Veijalainen presents a model of a carbon‐free power system to study the behavior of electricity storage in the case of Finland, optimizing storage, wind, and solar power, with varying background amounts of nuclear power and international transmission. Use of multi‐year data was found to be important to secure system availability in different weather conditions.